2016
DOI: 10.1093/ntr/ntw019
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Effects of Menthol and Nicotine in an E-Cigarette

Abstract: Introduction: Despite the longstanding use and popularity of menthol as a flavorant in tobacco products, its sensory interactions with inhaled nicotine have never been measured independently of the other irritants in tobacco smoke. We therefore measured the perception of menthol in an E-cigarette with the primary goal of assessing its analgesic effect on the sensory irritation produced by inhaled nicotine. Methods: Adult cigarette smokers sampled aerosolized E-liquids containing five different concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
94
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 52 publications
(59 reference statements)
9
94
1
1
Order By: Relevance
“…The doses of menthol selected were derived from a published dose-finding study employing solutions from the same source. 18 The high menthol dose produced a cooling effect comparable to that of a commercial solution (AmericaneLiquidStore™) of comparable concentration; the lower dose produced a minimally discernable effect when inhaled from a nicotine free solution. Commercial suppliers of e-cigarette solutions rarely indicate menthol concentrations.…”
Section: Methodsmentioning
confidence: 91%
“…The doses of menthol selected were derived from a published dose-finding study employing solutions from the same source. 18 The high menthol dose produced a cooling effect comparable to that of a commercial solution (AmericaneLiquidStore™) of comparable concentration; the lower dose produced a minimally discernable effect when inhaled from a nicotine free solution. Commercial suppliers of e-cigarette solutions rarely indicate menthol concentrations.…”
Section: Methodsmentioning
confidence: 91%
“…It is well established that menthol produces a cooling sensation along with a minty flavour 27. Previous studies have demonstrated that menthol has the effect of masking bitter taste and reducing harshness/irritation of cigarette smoke and nicotine 16 28–33. Furthermore, menthol tends to increase liking 16.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that menthol has the effect of masking bitter taste and reducing harshness/irritation of cigarette smoke and nicotine 16 28–33. Furthermore, menthol tends to increase liking 16. The improved sensory appeal of menthol cigarettes is greatest for youth, women and African-Americans,30 33–35 and the positive associations of menthol flavour in e-cigarettes demonstrated in this study suggest that these subpopulations may be at risk for greater rates of e-cigarette initiation and use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Menthol flavoring may increase e-cigarettes’ appeal, particularly at high nicotine concentrations. 16 Young adult cigarette smokers respond more to e-cigarette flavor availability than do older smokers, suggesting a role for flavors in attracting youth. 17 However, otherwise, there is a dearth of experimental research addressing how e-cigarette flavor affects e-cigarette use or abuse liability.…”
Section: Introductionmentioning
confidence: 99%